Intracellular increase of glutamate in neuroblatoma cells induced by polar substances of Galaxaura marginata (Rhodophyta, Nemaliales) - Rozas,Enrique E. (2008)
Four substances purified by HPLC from red seaweed Galaxaura marginata (Ellis & Solander) Lamouroux showed neuroprotective and mitochondria regulatory properties in neuroblastoma NEURO-2A cells line. Under oxidative basal conditions, each substance is capable of modifying the glutamate, glutamine and alanine intracellular concentrations, without to alter the oxidative equilibrium of these cells. These substances, also, produced a biphasic activity in the mitochondrial metabolism, inhibiting, in lower concentrations and stimulating, in higher concentrations the mechanism of cellular 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction, that indicates the mitochondrial activity. These data suggest that the intracellular increase of glutamate can be related to the glutamate/glutamine cycle alterations induced by the blockade of intracellular glutamate transport. Moreover, we suggested that there are substances, exhibiting neuroprotective activity in neuroblastoma cells, protecting them from oxidative stress produced by the inhibition of the glutamate transporters.